2006
DOI: 10.1590/s1676-24442006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Características da gastrite crônica associada a Helicobacter pylori: aspectos topográficos, doenças associadas e correlação com o status cagA

Abstract: Helicobacter pylori infection Chronic gastritis cagA-positive strains Pathogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…An investigation in other developing countries also showed a similar frequency (61.8%) [ 30 ]. In adults, a slightly higher frequency was found in other studies in Brazilian (88.4%) [ 31 ] and African (70–97%) populations [ 32 ]. These numbers most likely reflect the social and health conditions of the studied populations because infections by HP are more common in developing countries than in developed countries [ 19 ].…”
Section: Discussionmentioning
confidence: 51%
“…An investigation in other developing countries also showed a similar frequency (61.8%) [ 30 ]. In adults, a slightly higher frequency was found in other studies in Brazilian (88.4%) [ 31 ] and African (70–97%) populations [ 32 ]. These numbers most likely reflect the social and health conditions of the studied populations because infections by HP are more common in developing countries than in developed countries [ 19 ].…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have demonstrated that infections caused by cagA -positive H. pylori strains are associated with greater intensity of intestinal inflammation, activity, atrophy and metaplasia (1). According to Parsonnet and collaborators, patients infected by these strains would have a three times greater risk of developing gastric cancer (15).…”
Section: Discussionmentioning
confidence: 99%
“…The FOX test system was based on ferrous ion (Fe +2 ) to ferric ion (Fe +3 ) transformation by various types of peroxides in the samples analyzed. A purple-blue color complex (ferric-xylenol orange complex) was formed in the presence of ferric-xylenol, whose absorbance could be measured (Costa et al 2006). A special reagent that was prepared on the day of the analysis (the FOX reagent) is used in this method: solution A was prepared with 7.6 mg of xylenol orange and 88 mg of butylhydroxytoluene (BHT) in 90 mL of methanol; solution B was prepared with 9.8 mg of ferrous sulfate in 10 mL of 250 mM sulfuric acid (0.13 mL sulfuric acid in 10 mL water).…”
Section: Determination Of Total Hydroperoxide Concentration (Fox)mentioning
confidence: 99%
“…After this reading, a 25 µL aliquot of the stock solution of DTNB (10 nmol/L in absolute ethanol) was added to the solution, which was kept at room temperature for 15 min. After this period, a new reading was obtained using DTNB as the blank (Costa et al 2006). The concentration of sulfhydryl groups was calculated using GSH, and the result was reported as nmol/g protein.…”
Section: Determination Of Gsh Concentration -Total Concentration Of Tmentioning
confidence: 99%